The effect of Workplace Spirituality on Employee well-being, knowledge-Sharing Behavior, and Intention to Stay: Applied to hotels› sector in Sharm el-Sheikh city - Abdel-shakoor, Hany (The Arab Journal of Administration, 2023)
The hotel sector is considered one of the most important and most vital tourism sectors in both developing and developed countries, as it contributes in a large percentage to achieving economic growth. The most important key challenges facing the sector in how to move Intrinsic Motivation front lines and urged them to work, Although the previous literature gave full support to modern concepts in the field of positive organizational behavior, there is still a lot to know about these concepts, and in this context the concept of workplace spirituality provides a new vision as one of the concepts that is still not understood A limited and not integrated in the life of organizations, which did not receive the scientific attention deserving in our Arab environment, and this research examines the effect of workplace spirituality on employee well-being, knowledge sharing behavior and intention to stay, and the questionnaire was distributed to (384) workers in the hotels operating in Sharm El-Sheikh city (292) of which was completely retrieved, with an estimated response rate of (76%) constituting a response rate. The results revealed a direct impact of workplace spirituality on both employee well-being and knowledge sharing behavior, well-being was found to be related to intended to stay, but not arranged With the behavior of sharing their knowledge, In doing so, the research presents new insights about the reasons for moving intrinsic motivation of employee (workplace spirituality) and its role in achieving a better level of well-being, and this is first applied studies that test the joint effects of workplace spirituality and employee well-being on knowledge sharing behavior and intention to stay.